Intelligent Transportation Systems Using Big Data Analytics - S.G, Sowmiya Balasubramanian; Premkumar, Haripriya (International Journal of Psychosocial Rehabilitation, 2020)
Intelligent Transportation Systems are set to innovate and revolutionize the way current transportation systems work by creating safer and more efficient transportation methods. ITS generates large, rapidly increasing volumes of real time data from various sources which proves difficult to process and store. Real time data is very important for various traffic related applications and to solve various problems in day to day traffic scenarios. Innovative big data techniques are emerging rapidly in the field of ITS and are solving the problems which conventional systems cannot. In this paper, first we will touch upon the characteristic features of Big Data and Big Data analytics. Then the various Big Data platforms are discussed along with the data collection methods employed by Big Data Analytics. Finally, the various Big Data techniques which are popularly used for various ITS implementations are discussed.